2004
DOI: 10.1089/jmf.2004.7.467
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nicotine-Induced Toxicity by Curcumin and Curcumin Analog: A Comparative Study

Abstract: The present study was undertaken to evaluate the effects of curcumin and curcumin analog on blood oxidant-antioxidant status during nicotine-induced toxicity in male Wistar rats. Lung toxicity was induced by subcutaneous injection of nicotine at a dose of 2.5 mg/kg of body weight (5 days a week, for 22 weeks). The enhanced circulatory lipid peroxides in nicotine-treated rats was accompanied by a significant decrease in the levels of ascorbic acid, vitamin E, reduced glutathione, glutathione peroxidase, superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…This is in accordance with the reports that cigarette smoking results in decreased activities of scavenging enzymes [29,12]. Kalpana and Menon [21] have suggested that superoxide anion and hydrogen peroxide are the main source of nicotine induced free radical production depleting the cellular antioxidants. Supplementation of selenium enhanced the activity of scavenging antioxidant enzyme Means of three independent triplicates of the target genes were calculated, normalized with their corresponding GAPDH values.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with the reports that cigarette smoking results in decreased activities of scavenging enzymes [29,12]. Kalpana and Menon [21] have suggested that superoxide anion and hydrogen peroxide are the main source of nicotine induced free radical production depleting the cellular antioxidants. Supplementation of selenium enhanced the activity of scavenging antioxidant enzyme Means of three independent triplicates of the target genes were calculated, normalized with their corresponding GAPDH values.…”
Section: Discussionsupporting
confidence: 92%
“…Nicotine group: The female rats received a dose of nicotine (in physiological saline), (0.7 mg/kg body weight) daily with subcutaneous injection for 8 weeks [21].…”
Section: Animalsmentioning
confidence: 99%
“…The dose of curcumin used by us was based on its optimal anti-TGF-␤ effects at 5 mg/kg body wt in our preliminary experiments with 2.5, 5, and 20 mg/kg body wt. This dose is markedly lower than those used in adults by others, either by the oral or parenteral route (10,29). Our investigation into the mechanism of curcumin's protective effect on neonatal lung injury suggests blockage of hyperoxia-induced oxidative stress and TGF-␤ activation.…”
Section: Discussionmentioning
confidence: 65%
“…Curcumin has protective effect against cisplatin (Antunes et al, 2000), hydrocortisone (Ahmad et al, 2004), nicotine (Kalpana and Menon, 2004) (El-Ashmawy et al, 2006), ethanol (Naik et al, 2004) and irradiation (Thresiamma et al, 1998) induced damage in in vivo and in vitro test systems. Furthermore it has antimutagenic potential against cyclophosphamide and BAP induced genotoxicity in microbial and mammalian test systems (Shukla et al, 2002;.…”
Section: Introductionmentioning
confidence: 99%